Model Bisnis TikTok Shop dan Implikasinya terhadap Ekonomi Digital di Indonesia - Muhammad Agha Afkar; Yusmaneli (Yayasan Kawanad, 2023)
This research investigates the TikTok Shop business model and its implications for the digital economy in Indonesia. TikTok Shop, as an electronic commerce platform integrated with social media, introduces innovation by combining creative content and online shopping experiences. This research explores how TikTok Shop can increase market access for MSMEs, contribute to income, and accelerate digital economic growth in Indonesia. The findings show that TikTok Shop provides new opportunities for local businesses by providing a personal and interactive platform to promote products. However, the challenges of intense competition and the need for digital education are the focus of research to support long-term success. Strategic recommendations include marketing innovation, special education programs, and strengthening product authenticity policies to support TikTok Shop's continued growth. This research makes an important contribution to understanding the new dynamics in Indonesia's digital economy, providing insights for local business development and building a strategic framework for implementing supportive policies